Establishment of an in vitro propagation protocol for Thymus lotocephalus, a rare aromatic species of the Algarve (Portugal) - Coelho, Natacha (2013)
The aim of this work was to develop an in vitro propagation protocol for the endangered species Thymus lotocephalus using seedlings as explants. Several macronutrient concentrations of Murashige and Skoog medium (MS), cytokinin types and concentrations, and cytokinin/auxin combinations were tested to assess the shoots’ proliferation capacity. Although the best proliferation results were obtained with 6-benzyladenine, high percentages of hyperhidric shoots were observed. Because high proliferation of healthy shoots was observed in MS medium that was free of plant growth regulators, this medium was chosen for proliferation studies. The best rooting results were achieved in MS medium without auxins (92.00 ± 6.11%, 6.54 ± 0.52 and 1.60 ± 0.10 cm regarding rooting frequency, number of roots per shoot and longest roots, respectively) or supplemented with 0.5 mg l-1 indole-3-acetic acid (98.00 ± 2.11%, 11.14 ± 0.75 and 2.40 ± 0.24 cm, respectively). Plantlets were successfully acclimatised to ex vitro conditions with a survival rate of 93.33%. With the development of this micropropagation protocol, an important contribution has been made to the conservation of the endangered species T. lotocephalus.